(untitled) (Práxis Educativa, 2017)
The purpose of this article is to reflect on Teaching Work and its formative process through a bibliographical research. Initially, what is human social work is defined, both in its productive aspect and in its alienating form, and later, it is sought to understand the Teaching Work in its specificity and determinant aspects of capitalist society. From these studies, the relationship between theory and practice in teacher education is verified, considering the objective and subjective conditions inherent to the teaching and learning process, in which content and method are unified and complement each other, constituting reflexive praxis. In this case, it was concluded that dialectical logic is one of the possibilities of overcoming the division between theory and practice. Keywords: Teacher Training. Teaching. Reflective Praxis.